Sikap dan Motivasi Keluarga dalam Perawatan Penderita Diabetes Melitus di Wilayah Kerja Puskesmas Adimulyo: Family Attitudes and Motivation in Caring for Diabetes Mellitus Patients in the Adimulyo Community Health Center Working Area - Ernawati; Podo Yuwono; Devie Tika Sari (Journal of Holistics and Health Sciences (JHHS), 2023)
The prevalence of diabetes mellitus sufferers in Indonesia has reached more than 19.47 million people and is expected to increase to 28.57 million in 2045. Diabetes mellitus is a chronic disease characterized by an increase in blood sugar levels and requires treatment for a long time, even for life. sufferer's life. The family as the person closest to the sufferer has a family role and duty in helping care for DM sufferers undergoing treatment which can be done through the family's attitude and motivation. The aim of this research is to determine the attitudes and motivation of families in caring for family members suffering from DM in the Adimulyo Community Health Center working area. The method used is quantitative descriptive with a survey approach. The sample in this study was 80 respondents with a sampling technique using proportional random sampling. Data were collected using a family attitude and motivation questionnaire. The results of this research show that family attitudes are in the positive category (73.8%) and family motivation is in the strong category (65%). The research conclusion is that the family's attitude is in the positive category and the family's motivation is in the strong category. Future researchers can use different research methods to examine knowledge, behavior and family burden factors that influence DM care.   ABSTRAK Prevalensi penderita diabetes melitus di Indonesia mencapai lebih dari 19,47 juta orang dan diperkirakan akan meningkat menjadi 28,57 juta pada tahun 2045. Diabetes Melitus merupakan penyakit kronis yang ditandai adanya kenaikan kadar gula darah dan memerlukan perawatan dalam waktu yang lama bahkan bisa sampai seumur hidup penderita. Keluarga sebagai orang terdekat penderita memiliki peran dan tugas keluarga dalam membantu merawat penderita DM menjalani pengobatan yang dapat dilakukan melalui sikap dan motivasi keluarga. Tujuan penelitian ini, untuk mengetahui sikap dan motivasi keluarga dalam merawat anggota keluarga penderita DM di wilayah kerja Puskesmas Adimulyo. Metode yang digunakan deskriptif kuantitatif dengan pendekatan survey. Sampel dalam penelitian ini sejumlah 80 responden dengan teknik pengambilan sampel menggunakan proportional random sampling. Pengambilan data menggunakan kuesioner sikap dan motivasi keluarga. Hasil penelitian ini menunjukkan sikap keluarga kategori positif (73,8%) dan motivasi keluarga dalam kategori kuat (65%). Kesimpulan penelitian bahwa sikap keluarga dalam kategori positif dan motivasi keluarga dalam kategori kuat. Peneliti selanjutnya dapat menggunakan metode penelitian yang berbeda untuk meneliti faktor pengetahuan, perilaku, dan beban keluarga yang mempengaruhi perawatan DM.